Constructing the [parochial] global citizen. (20th October 2017) - Salter, Peta; Halbert, Kelsey
ABSTRACT: Cultural exchange is privileged in many higher education programs across the globe. The Australian government's New Colombo Plan refers to a 'Third Wave' of globalisation which foregrounds global interrelatedness through developing student capabilities to live, work and contribute to global communities and aims to make the global an 'everyday' experience for students. Mobility programs are promoted as the main strategy for fostering global perspectives, contradicting the idea of the global as an everyday experience. This paper unpacks constructs of global citizenship that underpin Australia's recent international and global engagement policies, and implications for the 'global' wave in 'local' parochial contexts.